2006
DOI: 10.1002/dc.20431
|View full text |Cite
|
Sign up to set email alerts
|

Is bacterial vaginosis associated with squamous intraepithelial lesion of the uterine cervix?

Abstract: The objective of this study was to analyze the association between bacterial vaginosis (BV) and squamous intraepithelial lesion (SIL). Pap smears were analyzed to verify the presence of BV and SIL. One hundred and ten women with SIL comprised the study group, while 110 women with no cytological abnormalities served as controls. BV was similarly present in women of both groups: 18% of women with SIL and 12% of women without SIL. Results were also similar when the grade of SIL was taken into consideration. BV wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
1
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 17 publications
2
21
1
3
Order By: Relevance
“…The lack of an association observed here for BV with high grade cervical lesions differs from the positive association found in a previous study in an HIV-seropositive population in Finland [10], and in populations from Brazil, Holland, and South Africa, in which HIV-status was unrecorded [7][8][9]14]. Our results are consistent, however, with those from two European studies with HIV status unknown [13,15], and three studies in the US, two with unknown HIV-status [6,12] and one with HIV-seropositive participants [16].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The lack of an association observed here for BV with high grade cervical lesions differs from the positive association found in a previous study in an HIV-seropositive population in Finland [10], and in populations from Brazil, Holland, and South Africa, in which HIV-status was unrecorded [7][8][9]14]. Our results are consistent, however, with those from two European studies with HIV status unknown [13,15], and three studies in the US, two with unknown HIV-status [6,12] and one with HIV-seropositive participants [16].…”
Section: Discussioncontrasting
confidence: 99%
“…Other factors acting in conjunction with HPV infection are likely involved in promoting the oncogenic capabilities of HPV, leading to the development of cancer. Coinfection of HPV with bacterial vaginosis (BV) has been suggested to advance this process and, for more than 25 years, has been considered a possible risk factor for cervical cancer development [6][7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…15,17,25,31,32 However, 2 studies showed similar frequencies of dysbacteriosis among women who had squamous intraepithelial lesions (SIL) compared with women who did not have SIL. 33,34 This discrepancy may be explained by the finding that the data in these studies were gathered simultaneously instead of over time. In addition, the presence of bacterial vaginosis was studied in women who already had cytologic abnormalities.…”
Section: Discussionmentioning
confidence: 96%
“…A study by Discacciati MG and at el, BV is associated with increased odds for prevalence and incidence of HPV as well as delayed clearance. 17 In this way BV, PID, STD, IUCD use, PTL, PRE_ PROM, elective termination of pregnancy, endometriosis, low birth weight, neonatal jaundice are associated with bacterial vaginosis.…”
Section: Outmentioning
confidence: 99%